Biogeography of Triatominae (Hemiptera: Reduviidae) in Ecuador : implications for the design of control strategies - Franch, Fernando Abad (2001)
Chagas disease control strategies strongly depend on the triatomine vector species involved in Trypanosoma cruzi transmission within each area. Here we report the results of the identification of specimens belonging to various species of Triatominae captured in Ecuador (15 species from 17 provinces) and deposited in the entomological collections of the Catholic University of Ecuador (Quito), Instituto Oswaldo Cruz (Brazil), the Natural History Museum London (UK), the London School of Hygiene and Tropical Medicine (UK), the National Institute of Hygiene (Quito), and the Vozandes Hospital (Quito). A critical review of published information and new field records are presented. We analysed these data in relation to the life zones where triatomines occur (11 life zones, excluding those over 2,200 m altitude), and provide biogeographical maps for each species. These records are discussed in terms of epidemiological significance and design of control strategies. Findings relevant to the control of the main vector species are emphasised. Different lines of evidence suggest that Triatoma dimidiata is not native to Ecuador-Peru, and that synanthropic populations of Rhodnius ecuadoriensis in southern Ecuador-northern Peru might be isolated from their sylvatic conspecifics. Local eradication of T. dimidiata and these R. ecuadoriensis populations might therefore be attainable. However, the presence of a wide variety of native species indicates the necessity for a strong longitudinal surveillance system.